Interleukin-30: A novel antiinflammatory cytokine candidate for prevention and treatment of inflammatory cytokine-induced liver injury - Dibra, Denada; Cutrera, Jeffry; Xia, Xueqing; Kallakury, Bhaskar; Mishra, Lopa; Li, Shulin (Hepatology (Baltimore, Md.), 2012)
The liver is the major metabolic organ and is subjected to constant attacks from chronic viral infection, uptake of therapeutic drugs, life behavior (alcoholic), and environmental contaminants, all of which result in chronic inflammation, fibrosis, and, ultimately, cancer. Therefore, there is an urgent need to discover effective therapeutic agents for the prevention and treatment of liver injury, the ideal drug being a naturally occurring biological inhibitor. Here we establish the role of IL30 as a potent antiinflammatory cytokine that can inhibit inflammation‐induced liver injury. In contrast, interleukin (IL)27, which contains IL30 as a subunit, is not hepatoprotective. Interestingly, IL30 is induced by the proinflammatory signal such as IL12 through interferon‐gamma (IFN‐γ) / signal transducer and activator of transcription 1 signaling. In animal models, administration of IL30 by way of a gene therapy approach prevents and treats both IL12‐, IFN‐γ‐, and concanavalin A‐induced liver toxicity. Likewise, immunohistochemistry analysis of human tissue samples revealed that IL30 is highly expressed in hepatocytes, yet barely expressed in inflammation‐induced tissue such as fibrous/connective tissue. Conclusion: These novel observations reveal a novel role of IL30 as a therapeutic cytokine that suppresses proinflammatory cytokine‐associated liver toxicity. (Hepatology 2012)